Giant dielectric behavior of BaFe0.5Nb0.5O 3 perovskite ceramic - Intatha U. (2014)
Single-phase cubic Ba(Fe,Nb)0.5O3 (BFN) powder was synthesized by solid-state reaction at 1443 K for 4 hour in air. X-ray diffraction indicated that the BFN oxide mixture calcined at 1200°C crystallizes to the pure cubic perovskite phase. BFN ceramics were produced from this powder by sintering at 1623-1673 K for 4 hrs in air. Samples prepared under these conditions achieved up to 94.7% of the theoretical density. The temperature dependence of their dielectric constant and loss tangent, measured at difference frequencies, shows an increase in the dielectric constant with temperature which is probably due to disorder on the B site ion of the perovskite. Non-Debye type of relaxation phenomena has been observed in the BFN ceramics as confirmed by Cole-Cole plots. The higher value of ε′ at the lower frequency is explained on the basis of the Maxwell-Wagner (MW) polarization model. © 2008 World Scientific Publishing Company.